Three nontrivial solutions for the p-Laplacian Neumann problems with a concave nonlinearity near the origin - Aizicovici, Sergiu (2012)
We consider a nonlinear Neumann problem driven by the p- Laplacian, with a right-hand side nonlinearity which is concave near the origin. Using variational techniques, combined with the method of upper-lower solutions and with Morse theory, we show that the problem has at least three nontrivial smooth solutions, two of which have a constant sign (one positive and one negative).